Multilateral aid agencies and strategic donor behaviour - George Mavrotas; Espen Villanger (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2006)
The paper builds on recent empirical evidence on the importance of strategic donor behaviour in aid allocation in order to develop a theoretical model where donor pressure on a recipient for influencing the aid disbursement of a multilateral institution is endogenously determined. Our game-theoretic, multi-agent model with one aid recipient, two bilateral donors and one multilateral institution illustrates the advantage of putting pressure on the recipient as an instrument for foreign policy, as seen from the mighty donor's point of view. The model shows how this strategic donor behaviour is damaging to the aid-recipient; we also show that other donors not sharing foreign policy goals similar to the strategic, influential donors will, in fact, reduce their aid contributions to the multilateral organizations. This may obviously have profound implications for the volume of total aid flows and may crucially undermine current efforts to substantially increase ODA to meet the Millennium Development Goals by 2015. Our paper also contributes to the common debate on foreign aid by presenting a rigorous model that explains the coexistence of both multilateral aid organizations and bilateral aid programmes.
Keywords: F35; 330; foreign aid; strategic donor behaviour; multilateral aid agencies; Entwicklungshilfe; Geberländer; Entwicklungsorganisation; Millennium Development Goals